Luces y sombras del periodismo ciudadano: actitud frente a un fenómeno imparable - Martínez Solana, Yolanda (Estudios sobre el Mensaje Periodístico, 2007)
The accelerated implantation of the digital media, the changes in the social habits and the perception by the citizenship of certain disfunciones in the traditional newspaper have caused the development of a new journalism with greater citizen participation. Nevertheless, the control absence could lead to errors and favour the manipulation. Since the basic principles of the journalistic communication continue being present, the traditional journalism can have a future if the necessary reforms in the editions and the communication enterprises policy are undertaken.